Physical Characterization of Bioplastics Made from Sweet Orange (Citrus sinensis) Peel Waste Pectin and Pandan Leaf (Pandanus amaryllifolius) Cellulose - Gabriella Marry Ayu; Nikmatul Khoiriah Harahap; Syarifah Riska Mela Putri (JURNAL BIOSAINS, 2026)
One effort to reduce environmental pollution is developing bioplastics from organic waste, such as pectin from sweet orange peel (Citrus sinensis) and cellulose from fragrant pandan leaves (Pandanus amaryllifolius). Pectin, a polysaccharide from orange peel, and cellulose from pandan leaves can produce biodegradable plastics easily decomposed by soil microorganisms. This study addresses the growing issue of plastic waste accumulation by creating eco-friendly packaging alternatives. Utilizing orange peel and pandan leaves aligns with the circular economy concept by turning food waste into valuable materials. The research aims to reduce plastic pollution and process organic waste into bioplastics based on pectin and cellulose. An experimental laboratory design using a Completely Randomized Design (CRD) was applied with pectin concentrations of 1 g, 2 g, and 3 g, each repeated three times. The formulation also included 1 g of pandan cellulose, carrageenan (0.8 g) as a stabilizer, and glycerol (2%) as a plasticizer. Data were analyzed using one-way ANOVA in SPSS 24. Results showed that increasing pectin concentration enhanced bioplastic thickness, reduced water absorption, and accelerated degradation over four weeks, indicating improved biodegradable performance.